Median Lethal Concentrations (LC50) of Chlorantraniliprole and Its Effects on Behavioral Changes - Naga Raju (Intelektual Pustaka Media Utama, 2013)
The aim of the present study was to determine the acute toxicity of chlorantraniliprole insecticide to the fresh water fish Labeo rohita. Environmental protection has attracted the attention of the wide cross-section of people all over the world which has now become a global issue amongst scientists and researchers working in this area. Experimental fish were exposed to different concentrations of chlorantraniliprole between range 0, 1, 2,34,5,6,8,10,12 and 13mg/L-1) for 96 hrs in test container. The 96hrs LC50 value of chlorantraniliprole (Coragen) on the fish was found to be 12.7mg/L-1. The variation in the LC values is due to its dependence upon various factors viz., sensitivity to the toxicant, its concentration and duration of exposure. Further study needs the processes by which these chemicals affect physiology and pathological changes and of fish and their bio-concentration and bio- accumulation in fish tissues.DOI: http://dx.doi.org/10.11591/ijphs.v2i4.4208